Pericytes modulate islet immune cells and insulin secretion through Interleukin-33 production in mice - Burganova, Guzel; Schonblum, Anat; Sakhneny, Lina; Epshtein, Alona; Wald, Tomer; Tzaig, Mika; Landsman, Limor (Frontiers in Endocrinology, 2023)
Immune cells were recently shown to support beta-cells and insulin secretion. However, little is known about how islet immune cells are regulated to maintain glucose homeostasis. Administration of various cytokines, including Interleukin-33 (IL-33), was shown to influence beta-cell function. However, the role of endogenous, locally produced IL-33 in pancreatic function remains unknown. Here, we show that IL-33, locally produced by pancreatic pericytes, is required for glucose homeostasis. To characterize pancreatic IL-33 production, we employed gene expression, flow cytometry, and immunofluorescence analyses. To define the role of this cytokine, we employed transgenic mouse systems to delete the Il33 gene selectively in pancreatic pericytes, in combination with the administration of recombinant IL-33. Glucose response was measured in vivo and in vitro, and morphometric and molecular analyses were used to measure beta-cell mass and gene expression. Immune cells were analyzed by flow cytometry. Our results show that pericytes are the primary source of IL-33 in the pancreas. Mice lacking pericytic IL-33 were glucose intolerant due to impaired insulin secretion. Selective loss of pericytic IL-33 was further associated with reduced T- and dendritic cell numbers in the islets and lower retinoic acid production by islet macrophages. Our study demonstrates the importance of local, pericytic IL-33 production for glucose regulation. Additionally, it proposes that pericytes regulate islet immune cells to support beta-cell function in an IL-33-dependent manner. Our study thus reveals an intricate cellular network within the islet niche.